The Role of Personality in Improving MSME Performance: Ontology, Epistemology, and Axiology Approaches - Prayogo Kusumaryoko; Sudarmiatin Sudarmiatin; Wening Padmi Rahayu (Mandalika Journal of Business and Management Studies, 2025)
This research aims to explore the role of personality in improving the performance of SMEs using a philosophical approach through the dimensions of ontology, epistemology, and axiology. The research problems include how personality affects SME performance and how the perspectives of ontology, epistemology, and axiology provide deeper insights into this relationship. The method employed is a Systematic Literature Review (SLR) by analyzing 25 international journal articless that discuss entrepreneurial personality, SME performance, and the underlying philosophical views. The results show that entrepreneurial personalities, such as proactiveness, openness to new experiences, and perseverance, play a significant role in enhancing SME performance. From an ontological perspective, personality is viewed as an entity influencing entrepreneurs' actions and decisions, while epistemology highlights that entrepreneurs' knowledge and experiences are crucial in shaping performance. Axiology emphasizes the ethical and social values underlying entrepreneurial actions in running a business. In conclusion, this study finds that a philosophical approach provides a more holistic understanding of the factors influencing SME performance. The implication of this research is the importance of developing entrepreneurial personalities as an effort to enhance SMEs' competitiveness and sustainability.